A hybrid beam-column element for direct second-order nonlinear analysis of PFRP frame structures. (1st September 2021) - Zhu, Ruijie; Li, Feng; Chen, Yan; Li, Ruoyu
Highlights: An novel nonlinear beam-column element for PFRP space frame structures is proposed. The detailed element formulations and element tangent stiffness matrix were derived. The connection system for PFRP profileswas incorporated into the element formula. The finally obtained hybrid beam-column element shows significant advantages. Abstract: In order to achieve accurate structural calculation of pultruded fiber reinforced polymer (PFRP) space frame structures by "a single element per member", an imperfect nonlinear beam-column element considering the hybrid effects of component stiffness is proposed. Based on the unique characteristics of PFRP profiles, the equilibrium differential equations considering transverse shear effect and initial deflection were established. Afterwards, the stability functions, bending functions, force versus deformation equations and element tangent stiffness matrix were further derived. With the consideration of common connection system for PFRP profiles, the effect of joint stiffness, rigid arm and reinforcement segment were incorporated into the element formula without increasing the external degrees of freedom: The effect of joint stiffness is considered by the static condensation procedure; The rigid arm effect is considered based on the relationship between end points of the rigid vector; The effect of reinforcement segment is considered based on the idea of equivalence. Besides, a novel 3D co-rotational procedure allowing for large load step was proposed to update the local-global transformation matrix. The finally obtained hybrid beam-column element was used for calculation of several PFRP structure verification cases, which showed the advantages of easy structural modelling, good accuracy and high computational efficiency.